Fluidic Manufacture of Star‐Shaped Gold Nanoparticles. Issue 41 (3rd July 2017) - Silvestri, Alessandro; Lay, Luigi; Psaro, Rinaldo; Polito, Laura; Evangelisti, Claudio
Abstract: Star‐shaped gold nanoparticles (StarAuNPs) are extremely attractive nanomaterials, characterized by localized surface plasmon resonance which could be potentially employed in a large number of applications. However, the lack of a reliable and reproducible synthetic protocols for the production of StarAuNPs is the major limitation to their spreading. For the first time, here we present a robust protocol to manufacture reproducible StarAuNPs by exploiting a fluidic approach. Star‐shaped AuNPs have been synthesized by means of a seed‐less protocol, employing ascorbic acid as reducing agent at room temperature. Moreover, the versatility of the bench‐top microfluidic protocol has been exploited to afford hydrophilic, hydrophobic and solid‐supported engineered StarAuNPs, by avoiding intermediate NP purifications. Abstract : Stars in‐flow : Anisotropic star‐shaped gold nanoparticles are synthesized by exploiting a microfluidic process. The seed‐less and user‐friendly protocol afforded highly reproducible and morphologically controlled nanoparticles. Moreover, different surface‐engineered nanoparticles can be obtained while avoiding time‐consuming purification steps.